Convergent cardiorespiratory neurons represent a significant portion of cardiac and respiratory neurons in the vagal ganglia - Devarajan, Asokan; Wang, Ke; Shannon, Kassandra; Su, Yujuan; Verheyden, Jamie; Sun, Xin; Vaseghi, Marmar (Frontiers in Cardiovascular Medicine, 2022)
Cardiorespiratory coordination is critical in maintaining physiological function in health and disease. Sensory neuronal "cross-talk" between the heart and the lungs is required for synchronous regulation of normal cardiopulmonary function and is most likely mediated by the convergence of sensory neural pathways present in the autonomic ganglia. Using neurotracer approaches with appropriate negative control experiments in a mouse model, presence of cardiorespiratory neurons in vagal (nodose) ganglia are demonstrated. Furthermore, we found that convergent neurons represent nearly 50% of all cardiac neurons and approximately 35% of all respiratory neurons. The current findings demonstrate a pre-existing neuronal substrate linking cardiorespiratory neurotransmission in the vagal ganglia and a potentially important link for cardiopulmonary cross-sensitization, which may play an important role in the observed manifestations of cardiopulmonary diseases.